Synthesis of U1 RNA in a DNA-dependent system from sea urchin embryos. - Morris, G F (1986)
A soluble extract prepared from blastula nuclei of sea urchin (Lytechinus variegatus) embryos accurately transcribes cloned sea urchin DNA. This extract synthesizes U1 RNA using a cloned U1 RNA gene as a template. The U1 RNA is initiated accurately, and a portion of the transcripts has the correct 3' end as judged by gel electrophoresis. Longer transcripts also are formed that extend at least 280 bases 3' of the gene, and some extend as far as 800 bases 3' of the gene. A template containing 203 bases 5' of the gene gave as efficient transcription as did the whole U1 gene. Accurate 3' end formation was obtained with a template extending only 34 bases 3' of the gene, but efficient 3' end formation required sequences between 34 and 67 bases 3' of the gene.